Pengaruh Keberagaman Gender Manajemen Puncak terhadap Financial Distress (Studi di Sektor Energi Indonesia) - Rangga Dhia Majduddin; Susanti (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
This article aims to determine the influence of gender diversity in the form of women's presence on the board of directors, board of commissioners and audit committee on the risk of financial distress faced by energy sector companies in Indonesia. The use of the board of commissioners and the audit committee is part of the latest research considering that Indonesia uses a two-tier system in top management structure. The sample of companies consist of 46 companies during the 2020-2022. The hypothesis in this paper will be tested using a logistic regression test. The findings of this paper show that gender diversity at the board of directors has a negative influence on the risk of financial difficulties faced by companies. Meanwhile, the gender diversity of the board of commissioners and the audit committee has no effect on financial distress. Further research is expected to develop the number of samples and update measurements with other methods.